Mathematical modeling and simulation of flow in domains separated by leaky semipermeable membrane including osmotic effect - Hron, Jaroslav; Neuss-Radu, Maria; Pustějovská, Petra (Applications of mathematics, 2011)
In this paper, we propose a mathematical model for flow and transport processes of diluted solutions in domains separated by a leaky semipermeable membrane. We formulate transmission conditions for the flow and the solute concentration across the membrane which take into account the property of the membrane to partly reject the solute, the accumulation of rejected solute at the membrane, and the influence of the solute concentration on the volume flow, known as osmotic effect.